The monster under the bed : how business is mastering the opportunity of knowledge for profit - Davis, Stanley M.; Botkin, James W. (New York : Simon & Schuster, 1995)
"Companies in the business of providing knowledge for profit will dominate the 21st-century global marketplace. And to stay competitive, these companies will increasingly play the major role in making education a lifelong learning process for consumers, employees, and students alike."--BOOK JACKET. "These are the startling trends revealed in this first in-depth study of the mushrooming knowledge-for-profit mega-industry that is already transforming the way we run our businesses and the way we learn. With knowledge doubling nearly every seven years, while the life cycles of businesses grow shorter and shorter, the best way to succeed in today's economy is to become a knowledge-based business - one that leverages the enormous economic value of knowledge. Utilizing the sophisticated tools and skills of the new information technology, any business can become a knowledge business
The proliferation of smart products and services makes it necessary to educate employees and consumers on their development and use.Stan Davis and Jim Botkin show you how to accomplish this. The Monster Under the Bed is packed with examples of companies like AT&T and Arthur Andersen that are riding the crest of this powerful new wave by creating and marketing products and services that make their customers smarter and their businesses more profitable."--BOOK JACKET. "The same forces that are driving knowledge-for-profit businesses are dramatically changing education as we have known it. The vast majority of the more than 60 million PC owners, for example, learned how to use their computers either at work or at home, not in school
Spending by American companies on employee education in one recent year alone was equivalent to funding thirteen new Harvards. Education-intensive companies like Motorola have found that they gain as much as $30 in productivity for every dollar they invest in employee training. Davis and Botkin explain the opportunities and pitfalls of this revolution in knowledge and learning. They explain how any high-tech, low-tech, or no-tech company can open up new markets and create new sources of income by building its business for the future on a knowledge-for-profit basis - and how, once it does this, its competitors must follow or fail."--BOOK JACKET.
"We are at a major turning point. For some people, the monsters are the dinosaurs in business and educational institutions that are not adapting to the new realities. Where others sense a threat, the authors see enormous opportunities. Visionary in its scope, informative and thought-provoking on every page, The Monster Under the Bed is an exploration of the many ways that the knowledge-for-profit revolution will profoundly affect our businesses, our educational processes, and our everyday lives. It is also a call to build and grow with knowledge-based technology, welcoming the future as a friend not a foe."--BOOK JACKET
Includes bibliographical references (p. [175]-177) and index.
Keywords: Business education; Business and education; Employees -- Training of; Information technology; Continuing education; Competition